Global Staffing - Soetjipto, Budi W. (Forum Manajemen, 1996)
The polycentric approach has its own disadvantages as well. Perhaps the major disadvantage is that of bridging the gap between HCNs at national subsidiaries and PCNs at corporate headquarters.